US Patent No. 8,706,430: Compensating for frequency change in flowmeters - Tombs, M (United States Patent and Trademark Office, 2014)
Motion is induced in a conduit that contains a fluid. The motion is induced such that the conduit oscillates in a first mode of vibration and a second mode of vibration. The first mode of vibration has a corresponding first frequency of vibration and the second mode of vibration has a corresponding second frequency of vibration. At least one of the first frequency of vibration or the second frequency of vibration is determined. A phase difference between the motion of the conduit at a first point of the conduit and the motion of the conduit at a second point of the conduit is determined. A quantity based on the phase difference and the determined frequency is determined. The quantity includes a ratio between the first frequency during a zero-flow condition and the second frequency during the zero-flow condition. A property of the fluid is determined based on the quantity.